Analysis of the Effect of Asset Growth and Total Asset Turnover (Tattoo) on Return On Asset (Roa) with Capital Structure as an Intervening Variable (Case Study on Kpri Dwija Karya Bantarbolang 2017-2021) - Eli Erfandi; Dian Murdianingsih; Triana Yus Setiani; Yosi Pupus Indriani (Return : Study of Management, Economic and Bussines, 2022)
The study entitled “Analysis of the Effect of Current Ratio and Total Asset Turnover (TATO) on Return on Asset (ROA) with Capital Structure as an Intervening Variable (Case study at KPRI Dwija Karya)”. The purpose of this study was to determine and analyze the effect of Asset Growth and Total Asset Turnover on Return on Asset mediated by Capital Structure, either directly or inderectly. The population used in this study is the Financial Statements at KPRI Dwija Karya Period 2017-2021. The sample used in this studywas purposive sampling techniques in the Annual Financial Report. This study uses Multiple Linier Regression Ananlysis with SPSS V.25 Application. The result of the study partially show that the Asset Growth (X1) variable has no significant effect on Return on Asset (Y) with a value (tcount 3,612 < ttable 1,984). the Total Asset Turnover variable (X2) shows a significant effect on Return on Asset (Y) with value (tcount 11,236 > ttable 1,67155), there is no significant effect between Current Ratio (X1) on Return on Asset (y) with Capital Structure (Z) as an intervening variable with a value (tcount -1,8486 < ttable 1,96) there is no significant effect between Total Asset Turnover (X2) on Return on Asset (Y) with Capital Structure (Z) as an intervening variable with a value (tcount 2,3472 > ttable 1,96), Capital Structure (Z) has a significant effect on Return on Asset (Y) with a value (tcount -2,702 > ttable 1,67155)